the values mirror of the soul and the contribution of initial educacation for its crystallization (Revista Electrónica REDINE, 2019)
The following essay, entitled the values ​​as a mirror of the soul and the contribution of initial education to its crystallization, develop the importance of education in values, from the early educational stages, which are vital in the formation of human beings and special influence for the good development of society and for the daily life. Educating a person implies the attention of the features that characterize it, which is why the values ​​are competences of the educational task, a fact that points to the concretion of a pedagogy conceived under parameters of tolerance and respect; That is why values ​​can be conceived as the principles and ends that inform or guide human, social and individual behavior. It is not possible to refer to values, if one does not think of a formative structure in which the principle and the center of action is man. Hence, values ​​represent lights in the darkness of people's lives and therefore must, from this perspective, truly appreciate them, they must be experienced; in such a way, that people conceive them as an esteemed and fruitful quality, such as honesty, tolerance, justice, responsibility, cooperation, solidarity, respect for life, friendship, peace, among others. Values ​​are the fundamental pillars of human behavior that grow if they feed, through family pedagogy, then through school and socializing processes.